Türkiye Kamuoyunda Dış Türkler algısına bir katkı: Birinci Dünya Savaşına kadar Türkistan Türkleri ile Türkiye Türklerinin ilişkileri ve savaşta Türkistanlıların desteği - (:unkn) unknown (My University, 2014)
Türkiye ve Türkistan aynı etnik köken, tarih, dil ve kültüre sahip iki coğ- rafyadır. XVI. yüzyılda kesintiye uğrayan bu coğrafyalar arasındaki ilişkiler, XX. yüzyıl başlarında büyük bir canlanmaya sahne olmuştur. Dönemin ulus- lararası gelişmeleri ile yükselen milliyetçilik düşüncesinin yanı sıra aydınlar ve basının etkisiyle ortaya çıkan bu tablo Birinci Dünya Savaşı sırasında büyük bir dayanışmayı ortaya çıkarmıştır. Çalışmada, üzerinde pek fazla durulmayan bu konu, Türkistan Türklerinin savaş sırasında Osmanlı Devletine destekleri ele alınmaktadır.

Turkey and Turkestan are two different regions with common ethnicity, his- tory, language and culture. Although the relations between the two regions were interrupted in the 16th century, a substantial revival was recorded in the early 20th century. During the First World War, a great solidarity emerged thanks to the rise of nationalism which was an outcome of international circumstances, along with the contributions by intellectuals and the press. This study deals with a matter that has attracted little attention, namely the support that Turks of Turkestan gave to the Ottoman Empire during the War.
The Support to Turkey Given by The People of Turkestan During the First World War as Part of the Perception of Outside Turks
Keywords: Tarih; Uluslararası İlişkiler; Siyasi Bilimler